2010
DOI: 10.1158/1538-7445.am10-lb-359
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-359: Plasma microRNAs as novel biomarkers for lung cancer

Abstract: Objective: Lung cancer is the leading cause of cancer-related deaths in both men and women. Since there is no validated population-based screening procedure, most patients with lung cancer are diagnosed at advanced stages with an overall five-year survival rate of only 15%. Therefore, diagnosis of lung cancer at an early stage is important for improving the outcome of patients. MicroRNAs (miRNAs), a family of 19- to 25-nucleotide and noncoding small RNAs that primarily function as gene regulators at post-trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(140 citation statements)
references
References 0 publications
3
135
0
2
Order By: Relevance
“…MiR-197 was found to be overexpressed in lung, prostate and pancreas cancer tissues compared with normal specimen, [17][18][19] while levels of circulating miR-197 in combination with other miRNAs were used to generate a signature of biomarkers for early detection of lung cancer. 20,21 Moreover, increased expression of miR-197 contributes to carcinogenesis and it is considered a reliable marker for diagnosis, patient stratification and prognosis assessment in follicular thyroid carcinomas, [22][23][24] while promoting EMT and metastasis in pancreatic adenocarcinoma. Supported by these in vitro results, we hypothesized that miR-197 targeting may exert a therapeutic activity by inhibiting tumor growth in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-197 was found to be overexpressed in lung, prostate and pancreas cancer tissues compared with normal specimen, [17][18][19] while levels of circulating miR-197 in combination with other miRNAs were used to generate a signature of biomarkers for early detection of lung cancer. 20,21 Moreover, increased expression of miR-197 contributes to carcinogenesis and it is considered a reliable marker for diagnosis, patient stratification and prognosis assessment in follicular thyroid carcinomas, [22][23][24] while promoting EMT and metastasis in pancreatic adenocarcinoma. Supported by these in vitro results, we hypothesized that miR-197 targeting may exert a therapeutic activity by inhibiting tumor growth in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these 3 miRNAs yielded 81.33% sensitivity and 86.76% specificity in discriminating lung cancer patients from controls. The levels of miR-155 and miR-197 were higher in the plasma from lung cancer patients with metastasis than in those without metastasis and were significantly decreased in responsive patients during chemotherapy (124). Different findings are reported by Heegaard et al that found that the expression of miRNA-146b, miRNA-221, let-7a, miRNA-155, miRNA-17-5p, miRNA-27a and miRNA-106a were significantly reduced in the serum of NSCLC cases while miRNA-29c was significantly increased.…”
Section: Specific Patterns Of Circulating Mirnas In Cancer Patientsmentioning
confidence: 92%
“…[40][41][42][43] However to date no systematic evaluation of miRNA profiles in matched tissue and plasma samples has been performed in EEC patients. The source of plasma miRNAs has not been determined so far.…”
Section: Early Detection and Diagnosismentioning
confidence: 99%